Growth and characterization of nanofibers obtained from isolated whey protein and polyethilene oxide by electrospinning technique (Superficies y Vacío, 2013)
In this work were obtained nanofi bers of whey protein isolated (WPI) and polyethylene oxide (PEO) using the electrospinning technique. For the preparation of the fi bers we started of dispersions of both materials by varying the proportion of PEOxWPI100-x, in the range of 0?x?100. The nanofi bers obtained were characterized by scanning electron microscopy, X-ray diffraction and theermogravimetric analysis.For values of x between 100% and 40% of PEO content, The fi bers growth with diameters average around the 230 ± 80 nm, whereas the dispersions with high content of WPI promote the formation of morphologies type ¨pearls¨. The crystallinity of the nanofi bers increased with the increases of PEO concentration in the solution. The nanofi bers obtained the combinations of PEO60WPI40 y PEO50WPI50were more thermally stable.